Smith Predictor: tuning considerations for performance and robustness enhancements - Martínez, Jesús; Camaeho, Oscar (Rev. Téc. Fac. Ing. Univ. Zulia)
The presence of delays in control loops is one of the main problems presented found in process industry. One of most popular delay time compensation scheme is the Smith predictor, but wrong controller’s tunings of the Smith predictor scheme can produce lower performances than the found using just a PID controller. In this paper are shown, firstly a wrong controller’s tunings, and secondly two techniques that improve the performance and the robustness of the control scheme. The tunings techniques are specifically designed for the controller that constitutes the Smith predictor scheme.